Surface-modified bioactive glass tooth desensitizer as well as preparation method and application thereof

By constructing the outer layer of polydopamine and gelatin on the surface of mesoporous bioactive glass and forming MBG@PDA@Gel nanoparticles, the problems of limited depth and unstable desensitization effect in existing bioactive glass are solved, and the problem of existing bioactive glass is limited in dentin tubules is achieved. Safe and long-term dentin tubular sealing and desensitization effects.

CN119385842APending Publication Date: 2025-02-07AFFILIATED STOMATOLOGICAL HOSPITAL OF NANCHANG UNIV (JIANGXI PROVINCIAL STOMATOLOGICAL HOSPITAL)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411538493.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The depth of existing bioactive glasses in dentin tubules is limited, making it difficult to maintain a long-term desensitization effect in a variable oral environment. At the same time, commonly used desensitizers have problems with microtoxicity and insufficient tolerance.

Method used

By constructing the outer layer of polydopamine and gelatin on the mesoporous bioactive glass surface, MBG@PDA@Gel nanoparticles are formed, enhancing their ability to enter dentin tubules and inducing hydroxyapatite generation within the tubules to clog tubules.

Benefits of technology

Under the influence of pH changes in the oral cavity and mechanical friction, it can effectively seal dentin tubules for a long time and safely provide long-term desensitization effect of dentin allergies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119385842A_ABST
    Figure CN119385842A_ABST
Patent Text Reader

Abstract

The invention discloses a surface-modified bioactive glass tooth desensitizer as well as a preparation method and application thereof, and belongs to the technical field of biomedical materials. The preparation method comprises the following steps: sequentially adding prepared MBG nanoparticles and dopamine hydrochloride into a Tris-HCI buffer solution, stirring at room temperature, centrifuging, collecting a product, washing, taking precipitate, adding deionized water, carrying out ultrasonic dispersion, dissolving gelatin into the deionized water, mixing with an MBG (at) PDA solution, stirring, centrifuging, collecting a product, washing, and carrying out vacuum freeze drying to obtain MBG (at) PDA (at) Gel powder. The medicine provided by the invention is a medicine for treating dentin hypersensitivity more safely and lastingly, so that generated mineral substances are tightly combined with dentin tubule walls, and long-acting dentin desensitization is realized by resisting a complex oral environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and more particularly to a surface-modified bioactive glass tooth desensitizer and a preparation method and application thereof. Background Art

[0002] Dentin hypersensitivity is a common oral disease in clinical practice, which seriously affects the daily life of patients. Conventional treatment methods mainly relieve discomfort by blocking exposed dentinal tubules or blocking nerve transmission, such as glutaraldehyde desensitizers that block dentinal tubules by precipitating proteins in dentinal tubules and desensitizers that reduce nerve excitability, or laser high heat field cauterization of the dentin surface to block dentinal tubules.

[0003] Ion exchange between bioactive glass (BG) and body fluids can induce the formation of HA through a series of biochemical reactions at the interface, thereby forming strong chemical bonds with bones and soft tissues, stimulating tissue repair and regeneration. BG also shows good therapeutic effects in dental tissue repair and regeneration, and has been shown to be able to induce mineral production to block dentinal tubules. The formation of mesoporous structure and pore volume increases bioactivity and makes nanoparticles more bioactive. Compared with BG, mesoporous bioactive glass (MBG) nanoparticles have stronger hydroxyapatite generation ability.

[0004] Gelatin has good biocompatibility and is often used for material surface modification. At the same time, because gelatin has more hydrophilic groups, it exhibits better fluidity, which is conducive to the diffusion and flow of modified drugs.

[0005] Polydopamine (PDA) and the repeated 3,4-dihydroxy-L-phenylalanine (DOPA) sequences in natural mussels both have excellent adhesion capabilities. This property of polydopamine can be used to construct a strong modified coating.

[0006] At present, the depth of bioactive glass entering the dentinal tubules is limited, and it can usually only cause the formation of minerals in the shallow layer of the dentinal tubules to block the dentinal tubules. Therefore, this desensitization effect is difficult to maintain for a long time in the changing oral environment. In addition, the desensitizers commonly used in clinical practice are often considered to have a certain degree of microtoxicity, which is believed to be harmful to the human body. In summary, there is an urgent need to find a material that can both block the dentinal tubules for a long time and is biocompatible, so as to safely and long-term treat dentin hypersensitivity.

[0007] Gluma desensitizers commonly used in clinical practice mainly rely on glutaraldehyde to induce plasma protein precipitation in dentinal tubules, thereby protecting the dental pulp nerves from external stimulation. Although Gluma desensitizers have long been considered effective for dentin hypersensitivity, Gluma desensitizers have poor tolerance to acid erosion and mechanical friction. More importantly, Gluma desensitizers are not suitable for long-term desensitization in the human body. Other desensitization methods such as laser desensitization are often considered to be a risky treatment method because of the high heat field they produce, which may cause damage to oral tissues.

[0008] Therefore, how to develop a surface-modified bioactive glass tooth desensitizer that is not affected by pH changes and mechanical friction in the oral cavity and can achieve safe and long-term desensitization of sensitive teeth, as well as its preparation method and application is an urgent problem that technicians in this field need to solve. Summary of the invention

[0009] In view of this, the present invention provides a surface-modified bioactive glass tooth desensitizer and a preparation method and application thereof.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] A method for preparing a surface-modified bioactive glass tooth desensitizer comprises the following steps:

[0012] (1) adding hexadecyltrimethylammonium bromide to deionized water and dispersing it ultrasonically until it is completely dissolved, adding ethyl acetate under magnetic stirring, stirring until microemulsion droplets are formed, adding ammonia water and continuing to stir, adding ethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate in sequence while continuing to stir, centrifuging after continuing to stir, collecting white precipitates, washing them alternately with ethanol and ultrapure water for multiple times, vacuum freeze-drying to obtain white powder, and calcining at high temperature to remove the template to obtain mesoporous bioactive glass nanoparticles MBG;

[0013] (2) The mesoporous bioactive glass nanoparticles and dopamine hydrochloride are sequentially added to a Tris-HCl buffer solution, centrifuged after magnetic stirring at room temperature, the product is collected, and washed multiple times with deionized water. All the precipitates after washing are added to deionized water for ultrasonic dispersion to obtain an MBG@PDA solution, gelatin is dissolved in deionized water, mixed with the obtained MBG@PDA solution, centrifuged after magnetic stirring, the product is collected, washed multiple times with deionized water, and vacuum freeze-dried to obtain an MBG@PDA@Gel powder, which is the surface modified bioactive glass tooth desensitizer.

[0014] Further, in step (1), 33 mL of deionized water, 10 mL of ethyl acetate, 7 mL of aqueous ammonia, 3.6 mL of tetraethyl orthosilicate (TEOS), 0.36 mL of triethyl phosphate (TEP) and 2.277 g of calcium nitrate tetrahydrate were added to every 0.7 g of hexadecyltrimethylammonium bromide (CTAB), and the concentration of the aqueous ammonia was 1 mol / L.

[0015] Further, in step (1), the magnetic stirring speed is 300-500 rpm, ethyl acetate is added, and stirring is continued for 30 minutes to form microemulsion droplets, ammonia water is added and stirring is continued for 15 minutes, and tetraethyl orthosilicate (TEOS), triethyl phosphate (TEP) and calcium nitrate tetrahydrate are added in sequence every 30 minutes while stirring is continued, and centrifugation is continued after stirring for 4 hours, the centrifugal speed is 9000 rpm, and the centrifugation is performed four times, each centrifugation time is 5 minutes, the high-temperature calcination temperature is 650°C, the high-temperature calcination time is 6 hours, the vacuum degree of vacuum freeze drying is ≤5 Pa, the vacuum freeze drying temperature is ≤-68°C, and the vacuum freeze drying time is 72 hours.

[0016] Further, in step (2), 200 mg of mesoporous bioactive glass nanoparticles and 200 mg of dopamine hydrochloride were added to every 100 mL of Tris-HCl buffer, all the precipitates after washing were added to 50 mL of deionized water for ultrasonic dispersion, 200 mg of gelatin was dissolved in deionized water and mixed with the obtained MBG@PDA solution, the concentration of the Tris-HCl buffer was 0.05 mol / L, and the pH was 8.5.

[0017] Furthermore, in step (2), the mesoporous bioactive glass nanoparticles and dopamine hydrochloride are sequentially added to a Tris-HCl buffer, the magnetic stirring speed is 400-500 rpm at room temperature, the stirring time is 12 hours, the centrifugal speed is 9000 rpm, and the centrifugal time is 5 minutes.

[0018] Furthermore, in step (2), all the washed precipitates are added to deionized water and ultrasonically dispersed at a power of 400 W for 15 minutes.

[0019] Furthermore, in step (2), gelatin is dissolved in deionized water and mixed with the obtained MBG@PDA solution at a magnetic stirring speed of 400-500 rpm, a stirring time of 12 hours, a centrifugal speed of 9000 rpm, a centrifugal time of 5 minutes, a vacuum degree of vacuum freeze drying of ≤5 Pa, a vacuum freeze drying temperature of ≤-68° C., and a vacuum freeze drying time of 72 hours.

[0020] The invention also provides a surface-modified bioactive glass tooth desensitizing agent prepared by the method.

[0021] The present invention also provides an application of the surface modified bioactive glass tooth desensitizing agent in the preparation of a dentin desensitizing therapeutic drug.

[0022] Beneficial effects of the present invention: The present invention uses polydopamine to construct a firm gelatin outer layer on the surface of mesoporous bioactive glass, obtaining gelatin-modified bioactive glass (MBG@PDA@Gel) that is easier to enter the dentinal tubules and induces the formation of hydroxyapatite in the tubules to tightly block the dentinal tubules. It is not affected by pH changes and mechanical friction in the oral cavity, and achieves safe and long-term desensitization of sensitive teeth. The present invention is a safer and more durable drug for treating dentin hypersensitivity, so that the produced minerals are closely combined with the walls of the dentinal tubules, resisting the complex environment of the oral cavity to achieve long-term desensitization of the dentin. Its superior closed desensitization effect over traditional Gluma desensitizers and the safety of laser treatment make it promising in the treatment of dentin desensitization. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 SEM (A) and TEM (B) images of the prepared MBG, MBG@PDA and MBG@PDA@Gel;

[0024] Figure 2 is the particle size of the prepared MBG, MBG@PDA and MBG@PDA@Gel;

[0025] Figure 3 Zeta potential (A), FTIR (B), XPS (C), and TG (D) results of the prepared MBG, MBG@PDA, and MBG@PDA@Gel;

[0026] Figure 4 Laser confocal images of demineralized dentin discs treated with fluorescently labeled MBG (A), MBG@PDA (B), and MBG@PDA@Gel (C);

[0027] Figure 5 SEM images of demineralized dentin discs in each group after 1 day (A) and 4 days (B) of mineralization, and dentinal tubule occlusion rate after 1 day (C) and 4 days (D) of mineralization;

[0028] Figure 6 SEM images of demineralized dentin disks in each group after mineralization for 7 days (A) and 14 days (B) and XRD results of dentin disks in each group after mineralization for 14 days (C);

[0029] Figure 7Mechanical properties of demineralized dentin discs and changes in air pressure values ​​of dentin discs after drug treatment in each group; (A) Nanoindentation results, (B) Elastic modulus and hardness results; (ND: natural dentin; ED: acid-etched demineralized dentin; M: MBG group; MP: MBG@PDA group; MPG: MBG@PDA@Gel group in Figure A and Figure B), (C) Dentin tubule permeation model diagram; (D) Air pressure values ​​of dentin discs in each group after treatment and after acid etching and mechanical friction (the red line is the air pressure value of normal dentin, and the green line is the air pressure value of acid-etched demineralized dentin);

[0030] Figure 8 The SEM images of the dentin disc surface and cross section in each treatment group after acid etching (A) and the dentinal tubule blockage rate (B);

[0031] Fig. 9 The SEM images of the surface and cross-section of the dentin disc in each treatment group after mechanical friction treatment (A) and the occlusion rate of dentin tubules (B);

[0032] Fig.10 Figures 1 and 2 are images of dentin disk fixation in the rat oral cavity (A), air pressure value of dentin disk after mineralization for 14 days (B), Vickers hardness result (C), and SEM images of the control group, MBG group, MBG@PDA group, and MBG@PDA@Gel group; Figures DG are scanning electron microscope images of the control group, MBG group, MBG@PDA group, and MBG@PDA@Gel group, respectively, and Figures HK are enlarged images of DG, respectively.

[0033] Fig.11 Cell live and dead staining, from left to right are control group, MBG group, MBG@PDA group, MBG@PDA@Gel group;

[0034] Fig.12 The CCK-8 results of drug co-culture for 1 day for each group;

[0035] Fig.13 HE staining of rat cheek and tongue mucosa tissue;

[0036] Fig.14 HE staining of rat heart (A), liver (B), and kidney (C). DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] The preparation method of the surface modified bioactive glass tooth desensitizer comprises the following steps:

[0040] (1) 0.7 g of hexadecyltrimethylammonium bromide (CTAB) was added to 33 mL of deionized water and ultrasonically dispersed until completely dissolved. 10 mL of ethyl acetate was added under magnetic stirring at a speed of 400 rpm and stirred for 30 minutes to form microemulsion droplets. 7 mL of 1 mol / L ammonia water was added and stirred for 15 minutes. 3.6 mL of tetraethyl orthosilicate (TEOS), 0.36 mL of triethyl phosphate (TEP) and 2.277 g of calcium nitrate tetrahydrate were added in sequence every 30 minutes while stirring was continued. After stirring for 4 hours, centrifugation was performed at a speed of 9000 rpm for four times, each time for 5 minutes. The white precipitate was collected and washed alternately with ethanol and ultrapure water for 3 times. The white powder was obtained by vacuum freeze drying at a vacuum degree of 5 Pa, a temperature of -68 °C, and a time of 72 hours. The template was removed by calcination at 650 °C in a muffle furnace for 6 hours to obtain mesoporous bioactive glass (MBG) nanoparticles.

[0041] (2) 200 mg of mesoporous bioactive glass (MBG) nanoparticles and 200 mg of dopamine hydrochloride were added to 100 mL of Tris-HCl buffer with a concentration of 0.05 mol / L and a pH of 8.5, respectively. The mixture was centrifuged at 9000 rpm for 5 minutes under magnetic stirring at room temperature for 12 hours. The product was collected and washed three times with deionized water. All the precipitates after washing were added to 50 mL of deionized water for ultrasonic dispersion to obtain MBG@PDA solution. The ultrasonic dispersion power was 400 W. The time is 15 minutes, 200 mg of gelatin (Gel) is dissolved in 50 mL of deionized water, mixed with the obtained MBG@PDA solution, and centrifuged after magnetic stirring at a speed of 450 rpm for 12 hours. The centrifugal speed is 9000 rpm and the centrifugal time is 5 minutes. The product is collected, washed with deionized water 3 times, and vacuum freeze-dried. The vacuum degree of vacuum freeze-drying is 5 Pa, the temperature of vacuum freeze-drying is -68°C, and the vacuum freeze-drying time is 72 hours to obtain MBG@PDA@Gel powder, which is a surface modified bioactive glass tooth desensitizer.

[0042] The obtained MBG@PDA@Gel powder was scanned by SEM and TEM. Figure 1 As shown in the figure, the gelatin surface is still spherical like MBG under SEM after surface modification, and the mesoporous structure of the nanoparticles modified with gelatin is fuzzier than that of MBG under TEM. The particle size and zeta potential data of the three materials are obtained using a nanoparticle size analyzer, as shown in the figure. Figure 2 As shown in Figure 2, the hydrodynamic size of nanoparticles modified with gelatin increased compared with that of MBG. Figure 3 As shown in A, the negatively charged MBG further increases in negative charge after being modified with gelatin on the surface. The chemical composition of the three materials was analyzed using a Fourier transform infrared spectrometer, as shown in Figure 3 As shown in B, in the spectrum of MBG@PDA@Gel, characteristic bands caused by Si-O and Si-O-Si vibrations at about 800 cm1 and 1080 cm1, respectively, and a - 1; X-ray photoelectron spectrometer is used to analyze the material elements, such as Figure 3 C shows that in the obtained spectrum, the N1s peak in the MBG@PDA@Gel spectrum is significantly enhanced compared with the N1s peaks of the MBG and MBG@PDA spectra, which confirms the successful grafting of gelatin molecules; the loading rates of the three materials from 30°C to 800°C were measured at a rate of 10°C / min under nitrogen protection using a thermogravimetric analyzer, as shown in Figure 3 As shown in D, under the same temperature conditions, MBG@PDA@Gel has the largest mass loss due to the loss of surface gelatin molecules.

[0043] (I) Specific process of in vitro dentinal tubule sealing treatment

[0044] 1) Fluorescent labeling to test drug distribution

[0045] Synthesis of fluorescent labeling materials

[0046] MBG was functionalized with amino groups using APTES. 0.3 g of the MBG obtained above was ultrasonically dispersed in 60 mL of anhydrous ethanol, 0.6 mL of APTES was added, and then refluxed at 80 ° C for 24 hours. The precipitate was collected by centrifugation, washed three times with ultrapure water, and freeze-dried to obtain MBG@NH2.

[0047] MBG@NH2, MBG@PDA, and MBG@PDA@Gel were dissolved in 10 mL of anhydrous ethanol. After uniform dispersion, 1.5 mg of FITC was added to the three solutions respectively. The mixture was stirred for 24 hours in a dark place using a magnetic stirrer, centrifuged (9000 rpm, 5 minutes), washed 3 times, and dried in a freeze dryer for later use.

[0048] Distribution of fluorescent markers on the surface of demineralized dentin disks

[0049] The three fluorescently labeled materials were coated on the surface of demineralized dentin discs at a concentration of 20 mg / mL (coating for 1 min each time, coating 3 times; n = 3). After coating, the dentin discs were rinsed with deionized water and dried in a vacuum oven. The longitudinal sections of the three groups of dentin discs were photographed using a laser confocal scanning electron microscope and the depth of the materials penetrating into the dentinal tubules was measured. Figure 4As shown. The laser confocal image of the MBG@PDA@Gel group (C) shows that compared with the MBG group (A) and the MBG@PDA group (B), more nanoparticles have entered the dentinal tubules, and more dentinal tubules have nanoparticles.

[0050] 2) In vitro demineralized dentin remineralization experiment

[0051] Demineralized dentin disc preparation

[0052] The third molars of upper and lower jaws were collected, and the surface tartar and soft tissue were scraped off, and then placed in 0.5% chloramine T solution for ultrasonic washing for 15 minutes. The crown part was separated from the tooth at the junction of enamel and cementum, and the dentin disk was cut out with a low-speed water-cooled diamond saw to obtain a 1mm thick dentin disk sample at the top of the pulp chamber. The samples were polished in sequence with SiC paper (600, 1000, 1500, 2000 grit) under running water. 35% phosphoric acid gel was used to acid-etch the dentin for 30 seconds, rinsed with deionized water, and ultrasonically washed for 15 minutes. The treated dentin disk was stored in deionized water at 4°C for later use.

[0053] Remineralization of demineralized dentin in vitro

[0054] The demineralized dentin discs were randomly divided into four groups for treatment (n=5): blank group (a small brush was dipped in deionized water and applied for 1 minute, three times), MBG group (a small brush was dipped in 20 mg / mL MBG and applied for 1 minute, three times), MBG@PDA group (a small brush was dipped in 20 mg / mL MBG@PDA and applied for 1 minute, three times), and MBG@PDA@Gel group (a small brush was dipped in 20 mg / mL MBG@PDA@Gel and applied for 1 minute, three times).

[0055] After cleaning the dentin with deionized water, the four groups of treated dentin sections were placed in artificial saliva at 37°C, and fresh artificial saliva was replaced every 24 hours.

[0056] On the first day of mineralization ( Figure 5 A) Day 4 Figure 5 B) Day 7 Figure 6 A) and Day 14 ( Figure 6 Scanning electron microscope images of the cross-section and longitudinal sections of the four groups of dentin disks were taken, and the images of the first day ( Figure 5 C) 4 days ( Figure 5The results of scanning electron microscopy images and calculation of dentinal tubule blockage rates showed that more dentinal tubules were blocked in the MBG@PDA@Gel-treated dentinal discs during the same mineralization period. At the same time, the scanning electron microscopy images on the 14th day of mineralization showed that the large dentinal tubules in the MBG@PDA@Gel group were basically completely blocked. At the same time, X-ray diffraction analysis was performed on the four groups of samples after mineralization for 14 days ( Figure 6 C) confirmed that the crystalline substance plugging the dentinal tubules was hydroxyapatite.

[0057] 3) Dentin tubule penetration test

[0058] For the four groups of dentin disks after 7 and 14 days of remineralization and the healthy dentin disks without acid etching, the air pressure values ​​were measured using the dentinal tubule penetration model (n=3), and the air tightness test was repeated five times for each sample.

[0059] Dentin tubule infiltration model Figure 7 C, and the measured air pressure values ​​of each dentin disk were processed and analyzed, and a dentin disk air pressure value bar graph was drawn ( Figure 7 D). It can be observed that the air pressure value of the dentin disc treated with MBG@PDA@Gel after 7 days of mineralization is close to that of the natural dentin disc, and the air pressure value measured by the dentin disc with extended mineralization time increases further.

[0060] 4) Mechanical properties of remineralized dentin

[0061] Nanoindentation tests were performed on the four groups of samples remineralized for 14 days and the unetched healthy dentin disks (n=3) after drying, with a loading time of 10 s, a holding time of 2 s, a Poisson's ratio of 0.28, and a loading force of 10 mN. Ten points were obtained for each sample.

[0062] The results of nanoindentation were analyzed and processed to obtain the load-displacement curve ( Figure 7 A), and calculate the elastic modulus and hardness of each group of samples ( Figure 7 B). Comparison of the elastic modulus and hardness of the samples in each group showed that the mechanical properties of demineralized dentin in the MBG@PDA@Gel group were restored to a higher degree, approaching the mechanical properties of natural dentin.

[0063] 5) Stability of dentin remineralization products

[0064] Acid resistance: The four groups of samples after remineralization for 14 days were treated with acid etching (immersion in 6% citric acid solution for 60 seconds; n = 3), and the occlusion of dentinal tubules in each group of samples under scanning electron microscopy before and after acid etching was compared ( Figure 8 A). The permeability of dentinal tubules in the four groups of samples after acid etching was also measured ( Figure 8 B).

[0065] Mechanical friction resistance: Four groups of samples remineralized for 14 days were mechanically brushed with a soft-bristled toothbrush for 3 minutes (n=3), and the occlusion of dentinal tubules under scanning electron microscopy of each group of samples before and after mechanical brushing was compared ( Fig. 9 A). At the same time, the permeability of dentinal tubules of the four groups of samples after mechanical brushing was measured ( Fig. 9 B).

[0066] The scanning electron microscopy surface and cross-sectional images of each sample after acid etching and mechanical friction treatment, as well as the calculated results of the dentinal tubule blockage rate of each group, show that the minerals produced by MBG@PDA@Gel that block the dentinal tubules have better stability than the minerals induced by MBG.

[0067] (I) The specific process of animal dentinal tubule sealing treatment is as follows:

[0068] SD male rats were selected and human dentin discs with holes were fixed inside the rats' mouths ( Fig.10 A), all dental discs were etched with 37% phosphoric acid to establish artificial demineralized dentin. The dentin discs were treated in the same way as the in vitro mineralized part. The control dentin samples were treated with deionized water. All rats were anesthetized by intraperitoneal injection of 1% sodium barbital (0.4mL / 100g). A 0.20mm stainless steel ligature was inserted into the interproximal space between the first and second molars of the rats, the ligature was connected to the dentin disc, and then to the upper central incisor. In order to make the process of tubule occlusion similar to that in the human mouth, the surface of each specimen was completely exposed to natural rat saliva (involving various enzymes and ions). The rats were fed soft food to avoid possible mechanical damage to the specimens.

[0069] After 14 days, the dentin disc samples were harvested, washed with deionized water and examined by SEM to obtain the control group ( Fig.10 D. Fig.10 H), MBG group ( Fig.10 E. Fig.10 I), MBG@PDA group ( Fig.10 F. Fig.10 J), MBG@PDA@Gel group ( Fig.10 G. Fig.10 K) SEM image (Figures H, I, J, and K are magnified images of the purple area in Figures D, E, F, and G, respectively). The hardness of the sample was tested using a Vickers hardness tester after 14 days ( Fig.10 C), and draw a bar graph. SEM shows that the minerals induced by MBG@PDA@Gel in the in vivo environment can tightly block the dentinal tubules; the dentinal disk air pressure test data ( Fig.10B) also shows that the air pressure value of the dentin disk treated with MBG@PDA@Gel in the in vivo environment is closest to the natural dentin disk. At the same time, the Vickers hardness test at this time also shows that MBG@PDA@Gel has the best treatment effect.

[0070] (III) Biocompatibility testing

[0071] 1) CCK-8 proliferation assay

[0072] MC3T3 cells were inoculated in a 96-well plate (5×103 cells / well) and cultured for 24 hours. Subsequently, the cells were cultured with three drugs at an incremental concentration of 400 μg / mL, and then cultured for 1 day. CCK-8 solution (10 μL) was added to each well, and cell proliferation was observed after 2 hours of culture. The absorbance at 450 nm was then recorded. Each experiment was tested three times.

[0073] The results of expressing the relative cell survival rate (%) at each concentration showed that regardless of MC3T3 ( Fig.11 ) showed good cell biocompatibility.

[0074] 2) Live and dead cell staining

[0075] Prepare AO / EB staining solution (protect from light): 90μl sterile water + 100μl C solution, mix well, add 5μl A solution + 5μl B solution, incubate for 20 minutes in the dark. Aspirate the old culture medium of the 96-well plate, wash twice with PBS (30 seconds), add 2mL of new culture medium, add 100μl AO / EB staining solution to each well, and take pictures with a fluorescence microscope after 30-60 seconds.

[0076] Cell live-death images show that almost no dead cells are visible, and MBG@PDA@Gel has no obvious toxicity to cells. Fig.12 )

[0077] 3) Organ toxicity test

[0078] Four groups of dentin samples were fixed in the oral cavity for 14 days and the rats were killed. Fig.14 ),tongue( Fig.14 ),Heart( Fig.14 A) Liver Fig.14 B) and kidney ( Fig.14 C), fixed in 4% formalin, processed, paraffin-embedded and sectioned, and all sections were stained with HE.

[0079] HE staining showed that there was no inflammatory response or other abnormalities in the stained sections of various tissues and organs in the MBG@PDA@Gel group, confirming that MBG@PDA@Gel has obvious organ biocompatibility. The above description of the disclosed embodiments enables professionals in the field to implement or use the present invention. Various modifications to these embodiments will be obvious to professionals in the field, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a surface-modified bioactive glass tooth desensitizer, characterized in that: The steps include: (1) adding hexadecyltrimethylammonium bromide to deionized water and dispersing it ultrasonically until it is completely dissolved, adding ethyl acetate under magnetic stirring, stirring until microemulsion droplets are formed, adding ammonia water and continuing to stir, adding ethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate in sequence while continuing to stir, centrifuging after continuing to stir, collecting white precipitates, washing them alternately with ethanol and ultrapure water for multiple times, vacuum freeze-drying to obtain white powder, and calcining at high temperature to remove the template to obtain mesoporous bioactive glass nanoparticles MBG; (2) The mesoporous bioactive glass nanoparticles and dopamine hydrochloride are sequentially added to a Tris-HCl buffer solution, centrifuged after magnetic stirring at room temperature, the product is collected, and washed multiple times with deionized water. All the precipitates after washing are added to deionized water for ultrasonic dispersion to obtain an MBG@PDA solution, gelatin is dissolved in deionized water, mixed with the obtained MBG@PDA solution, centrifuged after magnetic stirring, the product is collected, washed multiple times with deionized water, and vacuum freeze-dried to obtain an MBG@PDA@Gel powder, which is the surface modified bioactive glass tooth desensitizer.

2. The method for preparing a surface-modified bioactive glass tooth desensitizer according to claim 1, characterized in that: In step (1), 33 mL of deionized water, 10 mL of ethyl acetate, 7 mL of aqueous ammonia, 3.6 mL of ethyl orthosilicate, 0.36 mL of triethyl phosphate and 2.277 g of calcium nitrate tetrahydrate were added to every 0.7 g of hexadecyltrimethylammonium bromide, wherein the concentration of the aqueous ammonia was 1 mol / L.

3. The method for preparing a surface modified bioactive glass tooth desensitizer according to claim 1, characterized in that: In step (1), the magnetic stirring speed is 300-500 rpm, ethyl acetate is added, and stirring is continued for 30 minutes to form microemulsion droplets, ammonia water is added and stirring is continued for 15 minutes, and tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate are added in sequence every 30 minutes while stirring is continued, and centrifugation is performed after continuing stirring for 4 hours, the centrifugal speed is 9000 rpm, the centrifugation is performed four times, each centrifugation time is 5 minutes, the high-temperature calcination temperature is 650° C., the high-temperature calcination time is 6 hours, the vacuum degree of vacuum freeze drying is ≤5 Pa, the vacuum freeze drying temperature is ≤-68° C., and the vacuum freeze drying time is 72 hours.

4. The method for preparing a surface-modified bioactive glass tooth desensitizer according to claim 1, characterized in that: In step (2), 200 mg of mesoporous bioactive glass nanoparticles and 200 mg of dopamine hydrochloride are added to every 100 mL of Tris-HCl buffer, all the precipitates after washing are added to 50 mL of deionized water for ultrasonic dispersion, 200 mg of gelatin is dissolved in deionized water and mixed with the obtained MBG@PDA solution, the concentration of the Tris-HCl buffer is 0.05 mol / L, and the pH is 8.

5.

5. The method for preparing a surface-modified bioactive glass tooth desensitizer according to claim 1, characterized in that: In step (2), mesoporous bioactive glass nanoparticles and dopamine hydrochloride are sequentially added to Tris-HCl buffer, the magnetic stirring speed is 400-500 rpm at room temperature, the stirring time is 12 hours, the centrifugal speed is 9000 rpm, and the centrifugal time is 5 minutes.

6. The method for preparing a surface-modified bioactive glass tooth desensitizer according to claim 1, characterized in that: In step (2), all the washed precipitates are added to deionized water and ultrasonically dispersed at a power of 400 W for 15 minutes.

7. The method for preparing a surface-modified bioactive glass tooth desensitizer according to claim 1, characterized in that: In step (2), gelatin is dissolved in deionized water and mixed with the obtained MBG@PDA solution at a magnetic stirring speed of 400-500 rpm, a stirring time of 12 hours, a centrifugal speed of 9000 rpm, a centrifugal time of 5 minutes, a vacuum degree of vacuum freeze drying of ≤5 Pa, a vacuum freeze drying temperature of ≤-68° C., and a vacuum freeze drying time of 72 hours.

8. A surface modified bioactive glass tooth desensitizer prepared by the method according to any one of claims 1 to 7.

9. Use of the surface modified bioactive glass tooth desensitizer according to claim 8 in the preparation of a dentin desensitization therapeutic drug.

Citation Information

Cited By

  • High-stability tooth care paste containing bioactive glass

    CN122005363A